Imobilização de invertase bacteriana para a produção de açúcar invertido: influência do material de suporte e caracterização bioquímica - Saraiva, Larissa Santos (Universidade Federal do Tocantins, 2024)
Amazonian fruits have microorganisms capable of producing various enzymes, among which invertase stands out. Invertase catalyzes the hydrolysis of sucrose, potentially yielding inverted sugar and fructo-oligosaccharides. Given the inherent instability of soluble enzymes, immobilization can enhance stability, enabling reusability, reducing contamination, and minimizing byproduct formation, with careful selection of support material and immobilization method. This study aims to evaluate the immobilization process via physical adsorption and covalent binding of invertase produced by the bacterium Bacillus tequilenses, isolated from the Amazonian fruit pupunha, on support materials such as silica gel, polyhydroxybutyrate (PHB), and pure and glutaraldehyde-functionalized biochar. The objective is to obtain stable biocatalysts for sucrose hydrolysis into inverted sugar. Immobilization was conducted for 8 hours at 30°C using adsorption and covalent binding methods. Characterization of the biocatalyst involved operational stability, storage stability, pH stability (4.5 to 6.5), thermal stability (30°C to 60°C), and substrate concentration influence (5 g/L, 10 g/L, 20 g/L, 50 g/L, 100 g/L). After 8 hours of immobilization, a decrease in enzymatic activity was observed in the presence of supports, while the control sample maintained activity close to initial values. Enzymes immobilized on all three supports exhibited stability after 9 days of storage. For operational stability, immobilization on functionalized silica gel retained over 50% of its concentration until the third cycle. The biocatalyst was most stable between pH 5.0 and 6.0 when immobilized on functionalized PHB, whereas immobilization on functionalized silica gel showed higher activity at pH 5.0. During thermal stability, both functionalized supports exhibited higher activity at temperatures between 30°C and 50°C. With increasing substrate concentration, enzymatic activity increased in immobilizations with functionalized silica gel and PHB, with the latter demonstrating higher enzyme-substrate affinity according to kinetic parameters. These results indicate successful immobilization of bacterial invertase on all three supports, with high potential for obtaining stable biocatalysts for inverted sugar production.